2014
DOI: 10.1016/j.neuropsychologia.2014.02.019
|View full text |Cite
|
Sign up to set email alerts
|

One left dorsolateral prefrontal cortical HF-rTMS session attenuates HPA-system sensitivity to critical feedback in healthy females

Abstract: Abstract Abstract 2Objective: Although left dorsolateral prefrontal cortical (DLPFC) repetitive Transcranial Magnetic Stimulation (rTMS) is used to treat major depression, its underlying neurophysiological working mechanism remains to be determined. Prior research suggested that the clinical effects could be mediated by affecting the hypothalamic-pituitary-adrenal (HPA) system, but experimental studies in healthy individuals did not yield clear results. However, in healthy individuals, the influence of HFrTMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 71 publications
7
53
1
Order By: Relevance
“…Numerous studies have documented the role of prefrontal circuits in cognitive control (i.e., regulation) over stressful events (e.g., Baeken et al, 2014), as well as negative emotions (e.g., Leyman, De Raedt, Vanderhasselt & Baeken, 2011) and painful physical stimuli (e.g., Strigo, Simmons, Matthews, Craig & Paulus, 2008).…”
Section: Neurognitive Framework Regulation Expectationmentioning
confidence: 99%
“…Numerous studies have documented the role of prefrontal circuits in cognitive control (i.e., regulation) over stressful events (e.g., Baeken et al, 2014), as well as negative emotions (e.g., Leyman, De Raedt, Vanderhasselt & Baeken, 2011) and painful physical stimuli (e.g., Strigo, Simmons, Matthews, Craig & Paulus, 2008).…”
Section: Neurognitive Framework Regulation Expectationmentioning
confidence: 99%
“…In healthy samples, early studies found an increase in negative mood after stimulation of the left prefrontal cortex (George et al , 1996; Pascual-Leone et al , 1996; Dearing Martin et al , 1997), while more recent studies did not detect any changes in mood as a result of the stimulation itself (Mosimann et al , 2000; Grisaru et al , 2001; Padberg et al , 2001; Baeken et al , 2006, 2008; Baeken et al , 2014; Moulier et al , 2016). Schaller et al (2011) demonstrated that several sessions of HF rTMS attenuated only depression ratings of healthy individuals as assessed with the Becks Depression Inventory, while subjective mood ratings remained stable.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these findings, it is conceivable that HF rTMS over the left DLPFC has protective effects against a subsequent negative event. Indeed, recent studies have found that HF rTMS over the left DLPFC prior to a stress-inducing task attenuates subsequent decreases in heart rate variability (Remue et al , 2015) and stress hormonal responses (Baeken et al , 2014), as compared to stimulation over the right DLPFC and/or sham stimulation. Based on these considerations, the present study aims at investigating the effects of rTMS stimulation over the left DLPFC on affective responses to a negative mood induction and on attentional processing, which are both of direct relevance to emotion regulation in depression.…”
Section: Introductionmentioning
confidence: 99%
“…There are other mechanisms that might mediate the effect of rTMS and are probably independent of synaptic plasticity. For instance, rTMS has been shown to act on the neuroendocrine system by decreasing corticosteroid levels in rats and humans . Other effects include the prevention of neuronal death, as demonstrated by applying low‐intensity magnetic stimulation in cultures of cortical neurons, and increased expression of the glial fibrillary acidic protein in astrocytes .…”
Section: Why Rtms Might Be Used As a Therapeutic Toolmentioning
confidence: 99%